NILAI MEKANISTIK BETON ASPAL LAPIS PERMUKAAN TERHADAP PENGARUH TEMPERATUR DAN WAKTU PEMBEBANAN - M. Sjahdanulirwan; Nono Nono (Jurnal Jalan-Jembatan, 2009)
Performance of asphalt concrete largely depends on quality of aggregate, stiffness of bitumen and asphalt mixtures. This paper specifically discusses the effect of temperature and the loading time on mechanistic value of Asphalt Concrete Wearing Course (ACWC). Accoding to several literatures, in most ways asphalt stiffness is influenced by the time of loading and temperature which can influence mechanistic value of ACWC. To evaluate the effect of temperature and loading time on stiffness of asphalt and aspha lt mixtures, Van Der Poel’s Model is simulated. To evaluate the effect of temperature and loading time on tensile strain of ACWC, Shell’s model is applied.. Based on the analysis result, it is found that the effect of temperature on stiffness of asphalt penetration grade 60 is very significant, especially at temperature of more than 25°C. To maintain asphalt stiffness of 5 Mpa with loading time of 0.011 second (speed, V=80 km/hour) is 29.5°C. The effect of temperature and loading time on the stiffness of asphalt and asphalt mixtures is the same, both are very sensitive to the temperature of more than 25°C. Referring to Asphalt stiffness with minimum 5 Mpa, stiffness of ACWC is approximately 2250 Mpa.. ACWC fatigue will be sharter when temperature is colder and loading time is longer. Key words : mechanistic value, asphalt concrete wearing course, temperature, time of loading.